Dissertation Abstracts (Academy of Management Journal, 1965)
The article presents several abstracts dissertations in management research, including “The American Overseas Executive: An External Profile,” by Carlos J. Malferrari, “A History of Labor Unions in Mississippi,” by Donald Crumpton Mosley, and “The Grid Charting Technique for Management Information Systems,” by Gordon Thomas Shahin.